Hinge and ecomorphology of Legumen Conrad, 1858 (Bivalvia, Veneridae), and the contraction of venerid morphospace following the end-Cretaceous extinction. (May 2020) - Collins, Katie S.; Edie, Stewart M.; Jablonski, David
Abstract: The Veneridae are the most speciose modern family of bivalves, and one of the most morphologically conservative and homoplastic, making subfamily- and sometimes even genus-level classification difficult. The widespread Cretaceous genus Legumen Conrad, 1858 is currently placed in the subfamily Tapetinae of the Veneridae, although it more closely resembles the Solenoida (razor clams, Pharidae and Solenidae) in general shell form. Here we provide high-resolution images of the Legumen hinge for the first time. We confirm from hinge morphology that Legumen belongs in Veneridae, but it should be referred to incertae subfamiliae, rather than retained in the Tapetinae, particularly in light of the incomplete and unstable understanding of venerid systematics. Legumen represents a unique hinge dentition and a shell form—and associated life habit—that is absent in the modern Veneridae despite their taxonomic diversity. Veneridae are hyperdiverse in the modern fauna, but strikingly 'under-disparate, ' having lost forms while gaining species in the long recovery from the end-Cretaceous extinction.